Using Fables to Assist Students in Enhancing Their Reading Comprehension - Saputra, Frian; Kurniawati, Ari; Dewi, Nurmala; Nurhasanah, Indri; Hartati, Berli (CV. Doki Course and Training, 2023)
The main problem in this study was